Inflammatory Mediators in Tracheal Aspirates of Preterm Infants Participating in a Randomized Trial of Permissive Hypercapnia - Gentner, Sarah; Laube, Mandy; Uhlig, Ulrike; Yang, Yang; Fuchs, Hans W.; Dreyhaupt, Jens; Hummler, Helmut D.; Uhlig, Stefan; Thome, Ulrich H. (Frontiers in Pediatrics, 2017)
Background: Ventilator-induced lung injury is considered to be a main factor in the pathogenesis of bronchopulmonary dysplasia (BPD). Optimizing ventilator strategies may reduce respiratory morbidities in preterm infants. Permissive hypercapnia has been suggested to attenuate lung injury. We aimed to determine if a higher PCO2 target range results in less lung injury compared to the control target range and possibly reduces pro-inflammatory cytokines and acid sphingomyelinase (ASM) in tracheal aspirates (TA), which has not been addressed before. Methods: During a multicenter trial of permissive hypercapnia in extremely low birthweight infants (PHELBI), preterm infants (birthweight 400-1000 g, gestational age 23 0/7 – 28 6/7 weeks) requiring mechanical ventilation within 24 hours of birth were randomly assigned to a high PCO2 target or a control group. The high target group aimed at PCO2 values of 55-65, 60-70 and 65-75 mm Hg and the control group at PCO2 values of 40-50, 45-55 and 50-60 mm Hg on postnatal days 1-3, 4-6 and 7-14, respectively. TA were analyzed for pro-inflammatory cytokines from postnatal day 2 to 21. BPD was determined at a postmenstrual age of 36 weeks ± 2 days. Main findings: Levels of inflammatory cytokines and ASM were similar in both groups: interleukin (IL)-6 (p = 0.14), IL-8 (p = 0.43), IL-10 (p = 0.24), IL-1β (p = 0.11), macrophage inflammatory protein 1α (p = 0.44), albumin (p = 0.41), neuropeptide Y (p = 0.52), leukotriene B4 (p = 0.11), transforming growth factor-β1 (p = 0.68), nitrite (p = 0.15), ASM (p = 0.94). Furthermore, most inflammatory mediators were strongly affected by the age of the infants and increased from postnatal day 2 to 21. BPD or death was observed in 14 of 62 infants, which were distributed evenly among both groups. Conclusions: The results suggest that high PCO2 target levels did not result in lower pulmonary inflammatory activity and thus reflect clinical results. This indicates that high PCO2 target ranges are not effective in reducing ventilator-induced lung injury in preterm infants, as compared to control targets.